Developmental study on the regulation of neurotransmitter-sensitive adenylate cyclase systems in primary cerebral cell cultures from embryonic mice. Issue 7 (July 1985) - Shanker, Gouri; Pieringer, Ronald A.
Abstract : An ontogenetic study of the effect of various neuhormones and other activators on adenylate cyclase systems was carried out using cultures of ceils from 15-d-old embryonic mouse brain. Dopamine stimulated the enzyme activity at earlier culture ages (i.e. 4 and 10 d) but had little stimulatory effect at later ages (i.e. 20 and 33 d). Further, this stimulation at the earlier ages was blocked by the dopaminergic blocker, fluphenazine, but not by α and β-adrenergic antagonists. In contrast to dopamine, isoproterenol (a β-adrenergic agonist) had little stimulatory effect at earlier ages, but its ability to stimulate cyclase activity increased with age. This increase in all age groups was blocked by propranolol (afg – adrenergic antagonists). Epinephrine-sensitive enzyme activity showed a steady increase with age, which could be blocked with propranolol except in β-d-old cultures, where it was blocked instead by fluphenazine. Because the cultures are relatively enriched in neurons at earlier ages and in glia in later ages, the results suggest a predominantly neuronal localization for the dopamine sensitive adenylate cyclases and a glial localization of the isoproterenol and epinephrine sensitive adenylate cyclases. Histamine, serotonin, calcium/calmodulin and chloroadenosine were either only slightly or not at all stimulatory.